The role of humility in Chief Executive Officers: a review - Johannes Brunzel; Daniel Ebsen (Review of Managerial Science, 2022)
Humility, defined as a multidimensional construct comprising an accurate assessment of one's characteristics, an ability to acknowledge limitations and strengths, and a low self-focus, is a complex trait to potentially counterbalance detrimental effects of "negative" personal traits (e.g., narcissism), thereby making it relevant to researchers and practitioners in Management and Psychology. Whereas the study of the humility construct has become ubiquitous in Social Psychology, to our best knowledge, a review of the effects of humility in the contexts of company leaders (i.e., Chief Executive Officers) is lacking. Our systematic review suggests that CEO humility, directly and indirectly, affects a variety of individual, team, and organizational level constructs. Implications for research and practice are discussed, providing a future agenda for the construct to reach its full potential despite its relative novelty.
Keywords: 650; Humility; CEOs; Upper-Echelons; Top-management; Personality